2020
DOI: 10.4236/fns.2020.117053
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Characterization of Nine Cassava (<i>Manihot esculenta</i> Crantz) Cultivars from Chad

Abstract: In Chad, despite the multiple culinary uses of cassava leaves and tubers, their nutritional values are untapped. In this study, the physicochemical compositions and structure of nine cultivars were assessed. The proteins were obtained by Kjeldahl's method. Total sugars were determined according to the Luff-Schoorl method. For starch content, the polarimetric method of Earle and Milner was used. Mineral elements were carried out using an atomic absorption spectrophotometry. The cyanide was evaluated by the meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 24 publications
3
3
0
Order By: Relevance
“…The variations might be due to the mineral content of the soil from which the plants absorb their nutrients. The values were similar to those found by [28] in which the mineral concentrations of cassava root were Ca (22.4-238.6 mg/100g), Mg (24.52-165.22 mg/100g), Fe (75.38-606.37ppm), and K (22.42-22.44 mg/100g) and higher than that reported by [27] in which the content was between Ca(13.15-18.09mg/100g), Fe (0.00-0.01mg/100g), Zn (0.56-0.87mg/100g), and Mg (0.56-0.87mg/100g) (3.58-3.88). The values in this study were comparable with that reported by [29] in which the mineral contents were in the range between Ca(79.196-115.284mg/100g), Na(25.58-28.25ppm), K(69.28-76.41mg/100g), Fe(412.70-422.48ppm), Mg(31.76-33.34mg/100g), and Zn(17.52-22.46ppm).…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…The variations might be due to the mineral content of the soil from which the plants absorb their nutrients. The values were similar to those found by [28] in which the mineral concentrations of cassava root were Ca (22.4-238.6 mg/100g), Mg (24.52-165.22 mg/100g), Fe (75.38-606.37ppm), and K (22.42-22.44 mg/100g) and higher than that reported by [27] in which the content was between Ca(13.15-18.09mg/100g), Fe (0.00-0.01mg/100g), Zn (0.56-0.87mg/100g), and Mg (0.56-0.87mg/100g) (3.58-3.88). The values in this study were comparable with that reported by [29] in which the mineral contents were in the range between Ca(79.196-115.284mg/100g), Na(25.58-28.25ppm), K(69.28-76.41mg/100g), Fe(412.70-422.48ppm), Mg(31.76-33.34mg/100g), and Zn(17.52-22.46ppm).…”
Section: Resultssupporting
confidence: 91%
“…The variations might be due to the mineral content of the soil from which the plants absorb their nutrients. The values were similar to those found by [28] ). [19] in their investigation reported the mineral content of cassava leaves as K(1380-2260 mg/100g), Ca(430-1140 mg/100g), Mg(260-370 mg/100g), Na(38-120 mg/100g), Fe(15-27 mg/100g), and Zn(12-21 mg/100g).…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Maraphum et al [43] demonstrated that cassava starch contents present high variability, observing values in the range of 26.68-44.99%. These values are within the range observed in a study performed by Nadjiam et al, [44] where starch contents of different cassava cultivars ranged from 28.93% to 31.05%. It can be observed that the 23.2% content determined in our study is interesting, considering that this starch comes from the cassava peels, and that these are residues that are usually discarded.…”
Section: Physicochemical Properties Of Starchsupporting
confidence: 90%